Pengaruh DER, ROA dan EPS Terhadap PBV - Junaeni, Irawati; Megawati, Andriani (Business and Management Review, 2011)
Price to Book Value (PBV) is the ratio of the market value of equity to the book value of equity.  This ratio is frequently used as indicator of stock price or as a tool to measure intrinsic value of stock.  There are many factors that can affect PBV fluctuation.  This study will analyze both simultaneous and individual effect of Debt to Equity Ratio (DER), Return on Asset (ROA) and Earning Per Share (EPS) to Price to Book Value (PBV). The population in this study consists of all banks that are listed in Bursa Efek Indonesia (BEI) in the period of 2006-2010.  The sampling technique being used is ‘purposive sampling’ that results in 16 banks to be analyzed. There are four hypotheses developed in this study, i.e.: firstly, there is significant effect of DER, ROA and EPS to PBV; secondly, there is significant effect of DER to PBV; thirdly, significant effect of ROA to PBV and the last one is significant effect of EPS to PBV. Analysis method being used in this study is multiple regression analysis.  F-test is used to evaluate the simultaneous effect of independent variables to dependent variable and t-test is used to evaluate partial effect of each independent variable to dependent variable with level of significance 5%. As a result of this study, it is concluded that DER and ROA, individually, has no significant effect to PBV with level of significance more than 5%, while EPS has significant effect to PBV with level of significance less than 5%.  The simultaneous effect of DER, ROA and EPS to PBV is represented by adjusted R-square value at 0.174 or 17.4 %, and the remaining 82.6% is affected by other factors that are not emphasized in this study. The other factors could be as follows :Size, Devidend Payout Ratio (DPR), Beta Stock, Net Profit Growth Rate, Economic Value Added (EVA), Price Earning Ratio (PER), Loan to Deposit Ratio (LDR) and many other factors. Keywords : Debt to Equity Ratio (DER), Return of Asset (ROA), Earning Per Share (EPS) and Price to Book Value (PBV).